Technostress Creators, Technostress Inhibitors, and Transformational Leadership among Academic Administrators: Evidence from Preah Sihamoniraja Buddhist University, Cambodia - Sarom Mok; Bora Khath; Sothea Lim; Sereyrath Em; Darath Khim; Sokha Morn; Saravuth Um (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aimed to examine whether and to what extent Technostress Creators (TSC) and Technostress Inhibitors (TSI) predict the level of Transformational Leadership (TRL) among academic administrators at the Preah Sihamoniraja Buddhist University (PSBU) in Cambodia. Methodology: The study used a quantitative predictive correlational design with 123 PSBU academic administrators (e.g., rectors, deans, and department heads) selected through total population sampling. Data were collected using two instruments: the Technostress Creators and Inhibitors scale (TSC/TSI) and the Multiple-Factor Leadership Questionnaire (MLQ 5X) for transformational leadership. The instruments were back-translated and validated for clarity and reliability. Data were analyzed using descriptive and inferential statistics with computer-based methods. Main Findings: The findings revealed that techno-insecurity (T-INS) was the only statistically significant predictor, negatively associated with TRL. Other TSC and TSI variables were not statistically significant predictors. Overall, regression models for TSC and TSI did not significantly explain variation in TRL levels. Novelty/Originality of this study: This study is significant at the theoretical and practical levels. Theoretically, this study broadens the understanding of technostress and transformational leadership style. Practically, this study can be used to examine how academic administrators in higher education perceive technostress and its effects.